A Case of Polymicrobial Bacteremia in a Patient Undergoing Chemotherapy - Kyoko Arahata; Ryo Yamaguchi; Takeshi Terashima (Case Reports in Infectious Diseases)
We report an aggressive case of polymicrobial bacteremia in a patient with renal pelvis carcinoma. A 76-year-old man developed watery diarrhea after undergoing chemotherapy. He became unconscious and went into shock. Laboratory data showed severe neutropenia, renal failure, and lactic acidosis. Chest radiography showed multiple opacities. He died despite aggressive fluid resuscitation, catecholamine administration, antibiotic treatment, and mechanical ventilation. Blood culture isolates included Escherichia coli, Klebsiella pneumoniae, Streptococcus pneumoniae, Acinetobacter baumannii, and Moraxella catarrhalis. The foci of bacteremia were the respiratory tract and the bowel. The two infection foci and polymicrobial bacteremia are thought to be associated with the patient’s poor prognosis. Although polymicrobial bacteremia is rare, awareness of this condition and of the rare causative pathogens, such as A. baumannii and M. catarrhalis, especially in patients with comorbidities and immunosuppression will help treat the patients with bacteremia.